2005
DOI: 10.4314/thrb.v8i2.14279
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS and associated morbidity and mortality among hospitalised children in Kilifi, Kenya

Abstract: This study was carried to determine the frequency of HIV/AIDS and associated morbidity and mortality among children hospitalised in the paediatric ward at the Kilifi District Hospital, Kenya. All 7519 children admitted between January 2004 and June 2005 were eligible for the study. Testing for HIV antibodies was done using Determine and Unigold tests. Of the admitted children, 163 (2.2%) had clinical features of AIDS. Sixty (36.8%) of the HIV-positive children were below <18 months and 103 (64.2%) were ≥ 18 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…When analyzing for factors associated with HIV infection in this study it was found that, HIV-infected children were more likely to have lost a parent or both, present with cough, oral thrush, lymphadenopathy, acute malnutrition and stunting. These results are in line with those in previous studies describing the clinical presentation of HIV infection in children [ 5 , 13 , 14 , 18 22 ]. Hence, the presence of these associated factors should heighten the need to screen for HIV infection among children in settings where routine PITC services are not offered.…”
Section: Discussionsupporting
confidence: 93%
“…When analyzing for factors associated with HIV infection in this study it was found that, HIV-infected children were more likely to have lost a parent or both, present with cough, oral thrush, lymphadenopathy, acute malnutrition and stunting. These results are in line with those in previous studies describing the clinical presentation of HIV infection in children [ 5 , 13 , 14 , 18 22 ]. Hence, the presence of these associated factors should heighten the need to screen for HIV infection among children in settings where routine PITC services are not offered.…”
Section: Discussionsupporting
confidence: 93%
“…Our prevalence could have been higher if subjects with severe malnutrition with diarrhoea were screened prevalence rates as high as 10-30% have been recorded in several studies in Nigeria 3,7,9,16,17 and up to 50% in Ken-ya6 , 18 . Most of these studies involved other morbidities other than acute watery diarrhoea as in our study 3,6,7,16,17,18. In a Zambian study that assessed children 5 years and below with diarrhoea and HIV only 25% had acute diarrhoea, the remaining being chronic diarrhoea 9 .…”
Section: Discussionmentioning
confidence: 72%